KRITIK YUSUF AL-QARADAWI DI SEKITAR KOMPETENSI DAI DALAM BIDANG HADIS - Ahsan, Mohammad Nur (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2014)
This paper describes the criticism of Yusuf al-Qaradawi to the phenomenon of mistaken hadith quoting done usually by Muslim preachers. Although there is a controversy among the scholars of hadith about the use of weak hadths in terms of religious commands and prohibitons, al-Qaradawi considers it important for the Muslim preachers to equip themselves with knowledge of the issues summarized in the science of hadith, such as takhrij al-hadith and rijal  al-hadith.  This is recommended for the Muslim preachers to be careful of using weak hadiths denied because it contained falsehood. Yusuf al-Qaradawi offerred three additional requirements necessary for the preachers in this context. However, he rejected ethical recommendations for the preachers to quote weak hadiths either in sanad (chain of transmitters) or matn (the content of hadiths)